Effect of Storage and Priming on Seed Viability and Vigour in Khirni (Manilkara hexandra L.) - K. BHANUPRAKASH; H.S.YOGEESHA; M.N. ARUN; L.B. NAIK (Seed Research, 2026)
Khirni is a commercially important crop as it serves as a promising rootstock for sapota propagation. In the present investigation, studies were conducted to understand khirni seed viability during storage and their response to seed priming treatments. At the end of one year, seeds stored under ambient temperature and at 4°C lost viability whereas those stored at 15°C maintained germination up to 56 per cent. Priming with gibberellic acid and thiourea enhanced germination of six month old seeds stored at ambient conditions to the extent of 23 and 11 per cent, respectively. Further, priming improved seedling vigour both in fresh and aged seeds. The early seedling vigour obtained through seed priming in fresh and aged seeds could be exploited commercially for attaining graftable seedling size at the earliest to save nursery raising costs.